(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2024)
The implementation of Hindu piodalan in Bali varies from one region to another, this is because the traditions of each place are different, such as in Lemukih Village, Sawan District, Buleleng Regency, in every piodalan ceremony that is carried out there are traditions that are part of it. namely the metampelan tradition. Based on this, the problem formulation is as follows: 1. What is the form of implementation of the metampelan tradition in Lemukih Village, Sawan District, Buleleng Regency?, 2. What is the function of the metampelan tradition in Lemukih Village, Sawan District, Buleleng Regency?, 3. What is the function of the metampelan tradition in Lemukih Village, Sawan District, Buleleng Regency? The philosophical meaning of the metampelan tradition in Lemukih Village, Sawan District, Buleleng Regency? . After that, the data was analyzed through: data collection, data reduction, data presentation, and data conclusion. In the process of implementing the metampelan tradition, a process is put together so that the implementation goes well through the stages of the process of implementing the metampelan tradition, namely: the preparation stage, the implementation stage, and the final stage in The implementation of the metampelan tradition in Lemukih village, this cannot be separated from the time and place of implementation. The metampelan tradition has functions such as: the function of rejecting evil, the function of purification, the function of togetherness and the function of education. The philosophical meanings contained in the metampelan tradition are: the meaning of enriching religious kurtur in the metampelan tradition, the meaning of ethics and the meaning of cultural preservation